2015
DOI: 10.1155/2015/641784
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome of Severe Acute Malnutrition Cases at the Tamale Teaching Hospital

Abstract: Objective. This study investigated the treatment outcomes and determinant factors likely to be associated with recovery rate. Methods. A retrospective chart review (RCR) was performed on 348 patients who were enrolled in the outpatient care (OPC) during the study period. Results. Of the 348 cases, 33.6% recovered (having MUAC ≥125 mm), 49.1% defaulted, and 11.5% transferred to other OPC units to continue with treatment. There were 187 (53.7%) males and 161 (46.3%) females with severe malnutrition. The average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
34
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 13 publications
23
34
8
Order By: Relevance
“…Not only recovery and death rate but also the other outcome indicators in this study showed that there were in the minimum standard set of sphere project values/international standards [9]. The recovery rate in our study is higher than previous findings from Tigray [10], Kamba District [11], Uganda [12], Sudan [13], Tamale Teaching Hospital [14] and India [15]. But it is lower than findings from Jimma University Specialized Hospital [16], Woldiya General Hospital [17], Southern region of Ethiopia [18] and Rural Ethiopia [19].…”
Section: Discussioncontrasting
confidence: 54%
“…Not only recovery and death rate but also the other outcome indicators in this study showed that there were in the minimum standard set of sphere project values/international standards [9]. The recovery rate in our study is higher than previous findings from Tigray [10], Kamba District [11], Uganda [12], Sudan [13], Tamale Teaching Hospital [14] and India [15]. But it is lower than findings from Jimma University Specialized Hospital [16], Woldiya General Hospital [17], Southern region of Ethiopia [18] and Rural Ethiopia [19].…”
Section: Discussioncontrasting
confidence: 54%
“…The recovery rate in our study was good, 81% as against other studies where it was 33.6% in Mahama Saaka et al and 66% in Maurya et al [3,7] . The mean weight gain which was similar in our study when compared to other studies14gm/kg/day.…”
supporting
confidence: 63%
“…[8] The defaulter rate was better in our study, 5.8%, when compared to 53% in the Mahama et al study. [3] Limitation of our study was inadequate follow up. Hence, Hospital based management of these children in specialised feeding centre is very important for faster recovery and a better weight gain.…”
mentioning
confidence: 90%
“…The recovery rate in our study was good, 81% as against other studies where it was 33.6% in Mahama Saaka et al and 66% in Maurya et al 3,7 Major problems faced in NRCs was the duration of stay and also the mean weight gain which was low in our study when compared to other studies-14gm/kg/day, since most of the patients were opting for early discharge when once the complications were under control. 8 The defaulter rate was better in our study, 12.09%, when compared to 53% in the Mahama et al study.…”
Section: Discussionsupporting
confidence: 42%
“…Recovery rate may also vary in different NRCs. [2][3][4] Hence, this study was undertaken to know the outcome of SAM children admitted to the NRC of our hospital.…”
Section: Introductionmentioning
confidence: 99%